Pengaruh Media Papan Jurang (Penjumlahan dan Pengurangan) terhadap Hasil Belajar Siswa Kelas II A di SD Negeri 15 Sungailiat - Arzeta Maharani, Siti; Risnina Wafiqoh; Sisi Pitriyana (Universitas Muhammadiyah Bangka Belitung, 2025)
This study was motivated by the lack of enthusiasm of students when learning mathematics and the low learning outcomes of students on the material on how to calculate addition and subtraction, this can be seen from the minimum completeness criteria (KKM) which is still low because students are less interested in learning mathematics due to the lack of use of concrete media to make it easier for students to count. The purpose of this study was to determine the effect of the JURANG board media (addition and subtraction) on the learning outcomes of class II A students of Public Elementary School 15 Sungailiat.. This study is a quantitative study with a Pre-experimental design type, with One Group Pretest-Posttest. The sampling technique used a saturated sampling technique with samples of all class II A which became the experimental group. The data collection technique was carried out using essay questions. The data analysis technique used the normality test and the Paired Samples T Test hypothesis test.Based on the results of the normality test, the pretest data was 0.89 in the experimental class, for the posttest data in the experimental class 0.169, the data obtained was normally distributed because sig> 0.05. The results of the hypothesis test obtained a value of 0.00. So it can be concluded that there is an influence of the ravine board media (addition and subtraction) on the learning outcomes of Class II A students of Public Elementary School 15 Sungailiat.